(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article highlights the health-improving significance of gymnastics lessons in the physical development of primary school students. The study analyzed the impact of gymnastics exercises on children’s bodies, their role in increasing physical activity, and their potential in shaping a healthy lifestyle. In addition, methods for effectively organizing gymnastics lessons in primary grades were examined, and their pedagogical and health-improving aspects were substantiated. The results demonstrate that gymnastics lessons are an important factor in strengthening students’ physical development, movement coordination, and overall health.